Aktivitas Antioksidan Minyak Atsiri dan Ekstrak Etanol Kulit Batang Sintok (Cinnamomum sintoc Bl.) terhadap 1,1-difenil-2-pikrilhidrazil (DPPH) - Sri Adi Sumiwi; Anas Subarnas; Supriyatna Supriyatna; Marline Abdassah Bratadiredja (Indonesian Journal of Applied Sciences, 2011)
Sintoc (Cinnamomum sintoc Bl.) is a plant which is used as medicine. This plant has been known to have an analgesic antiinflamatory activity, therefore it is predicted to have an antioxidant activity. An investigation on antioxidant activity of sintoc essential oils and ethanolic extract of its cortex using ascorbic acid as standard has been carried out. Essential oils and ethanol extract of sintoc cortex was tested using DPPH (1,1-diphenyl-2-pikril-hidrazil) by measuring absorbance using visible spectrophotometer at 518 nm. The methods of this research were distillation of essential oils and extraction of sintoc cortex, determination of the essential oil and extract concentrations required for 50% inhibition of DPPH radical scavenging effect (IC50) with ascorbic acid as the possitive control. The variation concentration  of essential oils are 15, 5, 1, 0.1, 0.5 ppm and 25, 20, 17, 15, 10 ppm for ethanolic extracts. The results showed that the essential oil showed antioxidant activity with IC50 value was 16.29 ppm (5 times lower than ascorbic acid) and then ethanolic extract showed IC50 value 38.89 ppm (11 times lower than ascorbic acid, IC50 of ascorbic acid was 3.35 ppm).